Synthesis and evaluation of radiolabeled AGI-5198 analogues as candidate radiotracers for imaging mutant IDH1 expression in tumors. Issue 4 (15th February 2018) - Chitneni, Satish K.; Reitman, Zachary J.; Spicehandler, Rebecca; Gooden, David M.; Yan, Hai; Zalutsky, Michael R.
Graphical abstract: Abstract: Mutations in the metabolic enzyme isocitrate dehydrogenase 1 (IDH1) are commonly found in gliomas. AGI-5198, a potent and selective inhibitor of the mutant IDH1 enzyme, was radiolabeled with radioiodine and fluorine-18. These radiotracers were evaluated as potential probes for imaging mutant IDH1 expression in tumors with positron emission tomography (PET). Radioiodination of AGI-5198 was achieved using a tin precursor in 79 ± 6% yield (n = 9), and 18 F-labeling was accomplished by the Ugi reaction in a decay-corrected radiochemical yield of 2.6 ± 1.6% (n = 5). The inhibitory potency of the analogous nonradioactive compounds against mutant IDH1 (IDH1-R132H) was determined in enzymatic assays. Cell uptake studies using radiolabeled AGI-5198 analogues revealed somewhat higher uptake in IDH1-mutated cells than that in wild-type IDH1 cells. The radiolabeled compounds displayed favorable tissue distribution characteristics in vivo, and good initial uptake in IDH1-mutated tumor xenografts; however, tumor uptake decreased with time. Radioiodinated AGI-5198 exhibited higher tumor-to-background ratios compared with 18 F-labeled AGI-5198; unfortunately, similar results were observed in wild-type IDH1 tumor xenografts as well, indicating lack of selectivity for mutant IDH1 for this tracer. These results suggest that AGI-5198 analogues are not a promising platform for radiotracer development. Nonetheless, insights gained from this study may help in design and optimization of novel chemical scaffolds for developing radiotracers for imaging the mutant IDH1 enzyme.